A formula for simplicial tree-numbers of matroid complexes. (April 2016) - Kook, Woong; Lee, Kang-Ju
Abstract: We give a formula for the simplicial tree-numbers of the independent set complex of a finite matroid M as a product of eigenvalues of the total combinatorial Laplacians on this complex. Two matroid invariants emerge naturally in describing the multiplicities of these eigenvalues in the formula: one is the unsigned reduced Euler characteristic of the independent set complex and the other is the β -invariant of a matroid. We will demonstrate various applications of this formula including a "matroid theoretic" derivation of Kalai's simplicial tree-numbers of a standard simplex.